2001
DOI: 10.1509/jimk.9.2.1.19884
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Transfer as a Means for Relationship Development: A Kazakhstan–Foreign International Joint Venture Illustration

Abstract: Developing effective international joint ventures (IJVs) is critical for firms entering economies in transition, such as Kazakhstan. The resource-based view of the firm forms the foundation to examine the influence of knowledge transfer between IJV partners. Traditionally, the transfer of knowledge between IJV partners has been theorized to lessen dependence, increasing IJV instability. However, the relationship development literature indicates that the exchange of assets between partners can strengthen relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 59 publications
0
57
0
Order By: Relevance
“…Child (2000a) refers to such structural views of knowledge transfer and management learning as 'low context', because they tend to ignore the relevance of local factors to emerging business practices by emphasizing forms of economic, technological and/or psychological universalism. Criticized as mechanistic, shallow and de-contextualized (Djelic and Quack, 2002;Griffith et al, 2001), this concept of 'transfer' tends to ignore empirical counter-evidence that, for example, foreign ownership does not always effect the necessary changes in management and organization (Pollert, 1999), and may even bow in significant ways to local practices (Whitley and Czaban, 1998).…”
Section: Microeconomic Transformation and The Post-socialist Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Child (2000a) refers to such structural views of knowledge transfer and management learning as 'low context', because they tend to ignore the relevance of local factors to emerging business practices by emphasizing forms of economic, technological and/or psychological universalism. Criticized as mechanistic, shallow and de-contextualized (Djelic and Quack, 2002;Griffith et al, 2001), this concept of 'transfer' tends to ignore empirical counter-evidence that, for example, foreign ownership does not always effect the necessary changes in management and organization (Pollert, 1999), and may even bow in significant ways to local practices (Whitley and Czaban, 1998).…”
Section: Microeconomic Transformation and The Post-socialist Contextmentioning
confidence: 99%
“…In Western/post-socialist ventures, however, knowledge needs tend to be highly asymmetrical, because of systematic knowledge gaps that are typical of former SOEs (Griffith et al, 2001;Si and Bruton, 1999). While local partners need Western management expertise in order to survive, foreign partners see local knowledge -including cultural and language -as relatively insignificant in strategic terms, creating a balance of dependency of the local on the foreign partner.…”
Section: Structural Asymmetries In Western/post-socialist Venturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their satisfaction measure focused on the broad based evaluation of the IJV and the IJV relationship rather than performance. Ding (1997), Griffith et al (2001) and Lee and Beamish (1995) also used a perceptual measure of a parent's satisfaction with an IJV's performance (e.g., "To what extent has the IJV met the expectations of your firm?"). The main advantage of this type of measure is its ability to provide this type of information regarding the extent to which the IJV has achieved its overall objectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They have found that, compared with MNEs aiming for low marketing adaptation, those aiming for high adaptation are more likely to choose joint ventures (JVs) with local firms over wholly owned subsidiaries (WOSs) (Özsomer, Bodur, and Cavusgil 1991;Rau and Preble 1987). Such JVs allow adaptive MNEs to gain access to their partners' local market knowledge and brand names (Griffith, Zeybek, and O'Brien 2001;Tsang, Nguyen, and Erramilli 2004), thereby facilitating local marketing adaptation.…”
mentioning
confidence: 99%